2016
DOI: 10.1038/nmicrobiol.2016.57
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing metabolic pathways of hydrocarbon-degrading bacteria from the Deepwater Horizon oil spill

Abstract: The Deepwater Horizon blowout in the Gulf of Mexico in 2010, one of the largest marine oil spills(1), changed bacterial communities in the water column and sediment as they responded to complex hydrocarbon mixtures(2-4). Shifts in community composition have been correlated to the microbial degradation and use of hydrocarbons(2,5,6), but the full genetic potential and taxon-specific metabolisms of bacterial hydrocarbon degraders remain unresolved. Here, we have reconstructed draft genomes of marine bacteria enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
146
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 49 publications
5
146
1
Order By: Relevance
“…Genome assembly of Cycloloclsticus sp. Phe_8 by Dombrowski et al (37) was not included in our tree, because it was highly incomplete. Length of bar represents relative abundance of resolved genomes for each time point.…”
Section: The Initial Stage Of Low-molecular-weight Alkane Biodegradationmentioning
confidence: 99%
“…Genome assembly of Cycloloclsticus sp. Phe_8 by Dombrowski et al (37) was not included in our tree, because it was highly incomplete. Length of bar represents relative abundance of resolved genomes for each time point.…”
Section: The Initial Stage Of Low-molecular-weight Alkane Biodegradationmentioning
confidence: 99%
“…The study of interactions between microorganisms and OPs has primarily focused on microbial consumption of hydrocarbons in oil spills (Head et al, 2006;Mason et al, 2012). These bacterial groups have the capacity to use alkanes and PAHs as a carbon and energy source Dombrowski et al, 2016). These bacterial groups have the capacity to use alkanes and PAHs as a carbon and energy source Dombrowski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…17 (Grimaud et al, 2012) may have the capability to degrade PAHs and survive in rivers, lagoons, and seawater. Further studies using PAH-stable isotopes coupled with pyrosequencing (Dombrowski et al, 2016;Sauret et al, 2016) are necessary to identify the dynamics of these functional communities in the Términos Lagoon. Using similar approaches, previous reports have shown that the pollutant content and PAHs, in particular, were responsible for the bacterial community structure dynamic in the sediment of the Bizerte Lagoon, Tunisia (Ben Said et al, 2010).…”
Section: Biogeochemical Parameters and Pahs Drive The Prokaryotic Commentioning
confidence: 99%